Urgensi Pelatihan Penyusunan Laporan Keuangan Berbasis ISAK 35 Pada AUMDik Se-Kab. Jember - Diyah Probowulan; Dhian Wahana Putra (Jurnal Pengabdian Masyarakat Manage, 2023)
Muhammadiyah as a da'wah organization enforcer of truth and deterrent of ugliness committed to educating life based on tawhid and renewal. The renewal of Muhammadiyah in the field of education is to integrate faith, morals, and the progress of the education system. The Primary and Secondary Education Council (Dikdasmen) is actively trying to improve the management of Amal Usaha Muhammadiyah (AUM) in this field of education, especially in the financial management of Elementary schools, Junior High Schools, and Senior High Schools. AUM financial management has improved but has not been maximized, because there is still AUMDik di Jember Regency that does not prepare financial statements based on ISAK 35, this reporting is the basis for determining the amount of tax and for NIB management. This problem arises because almost 76% of school treasurers are occupied by someone who does not have accounting competence. This community service program was carried out to train AUMDik treasurers for the preparation of ISAK 35-based financial statements. The program implementation method involves school managers and the PDM Education Council, Jember Regency. The program starts with initial observation, problem formulation, socialization, mentoring, and reporting. The result of the assistance is an increase in the treasurer's ability to compile financial statements based on ISAK 35